APPLICATION OF GEOINFORMATICS FOR LANDSLIDE SUSCEPTIBILITY ANALYSIS IN KONKAN REGION, MAHARASHTRA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of this project is to delineate the susceptible zones near Kankavli railway station situated in Konkan region of Maharashtra. The Konkan region has a big railway transport mode that connects many big cities of Maharashtra with Konkan region. Konkan railway project in itself is a wondrous project in transportation sector. Due to heavy cutting of existing topography and unstable slopes the terrain is more prone to disasters such as landslides which often disrupt the smooth working of railway lines causing considerable damages to both life and property. Using geo informatics the region of railway track near Kankavli railway station was chosen to highlight the susceptible zones in that area so that preventive measures can be taken so as to prevent any further damages.